From Stress to Performance: Examining the Impact of Job Insecurity, Job Stress, Work Engagement, and Motivation on Employees of XYZ Bank - Theo Rizaldy Siahaan; Ardi Ardi; Sylvia Samuel; Richard Andre Sunarjo; Margaretha Pink Berlianto (Politeknik Siber Cerdika Internasional, 2026)
Background: The banking industry faces technological and economic pressures that affect employee performance. Job insecurity and job stress tend to reduce performance, while work engagement and motivation enhance it, making these factors important for effective HR strategies. Objectives: This study aims to examine the effects of job insecurity, job stress, work engagement, and motivation on the employee performance of XYZ Bank employees. Methods: The study was conducted using a quantitative approach with 127 XYZ Bank employees comprising the entire target population. Hypothesis testing was carried out using PLS-SEM analysis with SmartPLS software. Results: The results showed that job insecurity and job stress had a negative effect on employee performance, while work engagement and motivation had a positive effect on employee performance. Conclusion: The managerial implications of this study indicate that companies need to be transparent with employees about organizational conditions so that employees can understand and anticipate when the company will implement efficiency measures, thereby preventing feelings of job insecurity in the workplace.